The limits of resistance to criminal governance: cyclical violence and the aftermath of the autodefensa movement in Michoacán, Mexico - Herrera, Joel Salvador (Global crime, 2021)
This article asks whether some forms of collective action against criminal rule can mitigate or reduce violence. Focusing on the case of Michoacán, Mexico, this study examines the aftermath of an armed mobilisation against criminal governance that occurred between 2013 and 2014. It argues that the emergence of vigilante groups known as autodefensas was part of a regional cycle of violence where the rise to power of armed actors in Michoacán has repeatedly generated the conditions for their violent displacement by new actors. The autodefensas therefore failed to bring lasting public security as the cooptation and institutionalisation of the movement empowered new criminal groups in the region. Using municipal-level homicide data from 2015 to 2020, this study finds that municipalities where vigilante groups formed have experienced increasing levels of violence.